A simple combined approach using anterior transpetrosal and retrosigmoid approach: A case report - Tamura, Ryota; Ueda, Ryo; Karatsu, Kosuke; Sayanagi, Taichi; Takahara, Kento; Hino, Utaro; Iwama, Takashi; Nogawa, Hirotsugu; Nakaya, Masato; Horiguchi, Takashi; Toda, Masahiro (Frontiers in Surgery, 2023)
Background: Combined transpetrosal approach (CTP) is often used for large lesions in the posterior cranial fossa (PCF). Although CTP provides a wide surgical corridor, it has complex and time-consuming bony work of mastoidectomy, and cosmetic issues. Here, we describe a simple combined surgical technique to approach the supratentorial region, anterolateral surface of the brainstem, petroclival region and foramen magnum by drilling only petrous apex with a combination of retrosigmoid approach (RA). Clinical presentation: A 27-year-old female was refered with extra-axial left cerebellopontine angle (CPA) space-occupying epidermoid cyst extending to the prepontine cistern, anterior to the basilar artery, superior to the chiasma and caudally to the foramen magnum. A one-stage surgical procedure using anterior transpetrosal approach (ATP) and RA was performed after one-piece temporal-suboccipital craniotomy. These two approaches complemented each other well. Near-total removal was achieved. Conclusion: A one-stage surgical procedure using ATP and RA provides the wider viewing and better visualization of the PCF with minimal technical difficulty.